The Influence of Islamic Religious Education Learning in Forming Students' Character and Noble Morals - Nova Mutiara Dewi; Nahidah J. Abdulhassan; Hafiz Abdul Quddoos (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2025)
Purpose of the study: The purpose of this study is to see whether there is an influence of Islamic religious education learning on the morals of students at Widya Yahya Gading Rejo Vocational School, Pringsewu Regency. Methodology: The approach used is a quantitative approach. Data collection was carried out using a survey method with a questionnaire as an instrument to obtain X and Y data and analyzed using the product moment correlation analysis technique and tested with the t-test to determine the real level. Main Findings: The results of the correlation analysis showed an rxy value of 0.468, which is included in the moderate relationship category (0.400 – 0.599) and significant. The t-test test produced a t-count value of 4.620, which is greater than ttable (1.992) at a significance level of 0.05 with a degree of freedom (dk) of 78. This confirms the hypothesis that Islamic Religious Education learning has a positive influence on students' morals. The determination coefficient of 21.9% indicates that Islamic Religious Education learning affects students' morals by 21.9%, while 78.1% is influenced by other variables. Novelty/Originality of this study: This study provides innovation by specifically examining the influence of Islamic Religious Education learning on students' morals in the vocational school environment, which is still rarely done in the Pringsewu Regency area, and offers quantitative data as a basis for developing a religion-based education strategy.